2022
DOI: 10.1177/15459683221081430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Virtual Reality–Based Mirror Therapy Program on Improving Sensorimotor Function of Hands in Chronic Stroke Patients: A Randomized Controlled Trial

Abstract: Background. Embedding mirror therapy within a virtual reality (VR) system may have a superior effect on motor remediation for chronic stroke patients. Objective. The objective is to investigate the differences in the effects of using conventional occupational therapy (COT), mirror therapy (MT), and VR-based MT (VR-MT) training on the sensorimotor function of the upper limb in chronic stroke patients. Methods. This was a single-blinded randomized controlled trial. A total of 54 participants, including chronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Immersive VR systems have been developed to carry out mirror therapy with differing setups and rehabilitation protocols [25][26][27][28][29][30][31], including two described systems papers without any study results [27,28]. Weber and colleagues [25] presented a system which uses the Oculus Rift and its accompanying hand controllers to carry out mirror therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Immersive VR systems have been developed to carry out mirror therapy with differing setups and rehabilitation protocols [25][26][27][28][29][30][31], including two described systems papers without any study results [27,28]. Weber and colleagues [25] presented a system which uses the Oculus Rift and its accompanying hand controllers to carry out mirror therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The research found from the last 5 years is presented in the tables below (Tables 1 and 2). The longest study involving patients lasted 12 weeks [50], the shortest 2 weeks [48,49]. Only two studies included more than 50 patients [44,50].…”
Section: Resultsmentioning
confidence: 99%
“…The longest study involving patients lasted 12 weeks [50], the shortest 2 weeks [48,49]. Only two studies included more than 50 patients [44,50]. Four studies involved less than 20 patients in a research project [45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes were suggestive of short-term pain reduction, however, long-term effects are unknown. In studies of other conditions, immersive, interactive VR is a useful tool to prompt sensorimotor changes without active use of the affected limb, 83 and to influence nociceptive regulation via distraction. 84 More studies exploring its use and clinical feasibility with CRPS are required.…”
Section: Discussionmentioning
confidence: 99%